Development of a cancer-specific survival assessment for lymph node-positive colorectal cancer patients treated with adjuvant chemotherapy - Zhang, Lei; Gao, Shuang; Lin, Xiaoyuan; Hu, Junjie; Zhang, Guolin; Tang, Wei; Hu, Yubo; Wang, Yuanpeng; Chu, Liang (Frontiers in Surgery, 2025)
BackgroundTo construct a prognostic model for predicting cancer-specific survival in lymph node-positive colorectal cancer patients treated with adjuvant chemotherapy after surgery.MethodsData were collected from the 2010–2015 SEER database and from CRC patients at the Second Affiliated Hospital of Bengbu Medical University (2017–2023). Lasso regression and random survival forest methods were used to screen ten clinicopathologic features. Cox regression analysis identified independent prognostic factors for CRC. Nomogram plot model was used to predict 1-, 3-, and 5-year survival rates, with its accuracy verified through ROC curves, calibration curves, and decision curve analysis (DCA). The X-tile software differentiated between high and low-risk groups and illustrated survival differences using Kaplan–Meier curves.ResultsAge, histologic grade, stage, CEA, nerve invasion, and LNR were independent prognostic risk factors for colorectal cancer (P < 0.001); and LNR were the five variables used to construct the Nomogram. The area under the curve (AUC) was 0.83, 0.85, and 0.84 at 1, 3, and 5 years for the training cohort; 0.83, 0.85, and 0.84 at 1, 3, and 5 years for the internal validation cohort; and 0.83, 0.85, and 0.84 at 1, 3, and 5 years for the external validation cohort, respectively. calibration curves, C-indexes, and DCA curves validated the accuracy of the model, respectively. The survival prognosis of the high-risk group was lower than that of the low-risk group in all three data sets. (HR = 6.37, CI:6.05–6.71, P < 0.05; HR = 7.05, CI:6.52–7.64, P < 0.05; HR = 2.69, CI:1.66–4.37, P < 0.05)ConclusionsLNR represents a new independent prognostic factor for lymph node-positive CRC. The optimal threshold determined by the Nomogram method effectively categorizes subgroups of lymph node-positive CRC cases after surgical chemotherapy, crucial for guiding clinical treatment strategy selection.